Variability of sea salts in ice and firn cores from Fimbul Ice Shelf, Dronning Maud Land, Antarctica - Vega Riquelme, Carmen Paulina (2018)
Major ions were analysed in firn and ice cores located at Fimbul Ice Shelf (FIS), Dronning Maud Land – DML, Antarctica. FIS is the largest ice shelf in the Haakon VII Sea, with an extent of approximately 36500km2. Three shallow firn cores (about 20m deep) were retrieved in different ice rises, Kupol Ciolkovskogo (KC), Kupol Moskovskij (KM), and Blåskimen Island (BI), while a 100m long core (S100) was drilled near the FIS edge. These sites are distributed over the entire FIS area so that they provide a variety of elevation (50–400ma.s.l.) and distance (3–42km) to the sea. Sea-salt species (mainly Na+ and Cl−) generally dominate the precipitation chemistry in the study region. We associate a significant sixfold increase in median sea-salt concentrations, observed in the S100 core after the 1950s, to an enhanced exposure of the S100 site to primary sea-salt aerosol due to a shorter distance from the S100 site to the ice front, and to enhanced sea-salt aerosol production from blowing salty snow over sea ice, most likely related to the calving of Trolltunga occurred during the 1960s. This increase in sea-salt concentrations is synchronous with a shift in non-sea-salt sulfate (nssSO42−) toward negative values, suggesting a possible contribution of fractionated aerosol to the sea-salt load in the S100 core most likely originating from salty snow found on sea ice. In contrast, there is no evidence of a significant contribution of fractionated sea salt to the ice-rises sites, where the signal would be most likely masked by the large inputs of biogenic sulfate estimated for these sites. In summary, these results suggest that the S100 core contains a sea-salt record dominated by the proximity of the site to the ocean, and processes of sea ice formation in the neighbouring waters. In contrast, the ice-rises firn cores register a larger-scale signal of atmospheric flow conditions and a less efficient transport of sea-salt aerosols to these sites. These findings are a contribution to the understanding of the mechanisms behind sea-salt aerosol production, transport and deposition at coastal Antarctic sites, and the improvement of the current Antarctic sea ice reconstructions based on sea-salt chemical proxies obtained from ice cores.